Education Policy Issues and Political Influence - Ahmad Arif Billah; Fatihul Fauzi; Masduki Duryat (al-Afkar, Journal For Islamic Studies, 2026)
This article discusses issues of education policy that are always important topics of discussion in the dynamics of a country's development. Education is never free from political intervention, because education is a vital instrument in shaping human resources and the direction of the nation's future. This article discusses in depth issues of education policy in Indonesia and the influence of politics in its formation, both in terms of ideology, policy implementation, and curriculum revisions that often depend on the ruling political climate.